A Tour of the Missions: Observations and Conclusions - Strong, Augustus Hopkins, 1836-1921 (Salt Lake City, UT : Project Gutenberg, 2008)
"A Tour of the Missions: Observations and Conclusions" by Augustus Hopkins Strong is a travelogue written in the early 20th century. The author shares his experiences during a global tour of various missionary activities, focusing particularly on regions in Asia such as Japan, China, and Burma. Through his journey, Strong reflects on the work of missionaries, their challenges and successes, and the cultural landscapes they navigate, highlighting the profound need for spiritual guidance amid diverse religious practices and moral challenges. The opening of the text presents Augustus Hopkins Strong's motivations for embarking on the journey after years of teaching at the Rochester Theological Seminary and being encouraged by former students who became missionaries. He articulates the importance of firsthand observations and interactions with missionaries in their respective regions. Strong describes his experiences in Japan, where he navigates both the beauty of the landscape and the complexities of its religious environment. He reflects on the connections made during receptions with educated groups and highlights the impression made by local customs and traditions. His writing captures not only the logistical aspects of travel but also the spiritual and social reflections arising from his encounters with both missionaries and local communities. (This is an automatically generated summary.)
Release date is 2008-12-08
E-text prepared by a Project Gutenberg volunteer from digital material generously made available by
Keywords: Missions; East Asia -- Description and travel